2015
DOI: 10.1039/c4dt02047b
|View full text |Cite
|
Sign up to set email alerts
|

Reticular three-dimensional 3d–4f frameworks constructed through substituted imidazole-dicarboxylate: syntheses, luminescence and magnetic properties study

Abstract: A family of heteronuclear metal organic frameworks (MOFs) using lanthanide and transition metal ion based on a rigid ligand of substituted imidazoledicarboxylic acid, namely, {[Ln2Zn2 (μ3-Hmimda)2 (μ3-mimda)2·4H2O]n·mn H2O}, Ln = Nd, m = 2 (1), Ln = Ho, m = 3 (2), Ln = Er, m = 2 (3), Ln = Yb, m = 3 (4), [Tb2Co2(μ3-Hmimda)2 (μ3-mimda)2·4H2O]n·2nH2O} (5) and [Dy2Co2 (μ3-Hmimda)2 (μ3-mimda)2·4H2O]n·nH2O} (6), (H3mimda = 1H-2-methyl-4,5-imidazole-dicarboxylic acid), have been developed and characterized. All the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(46 citation statements)
references
References 122 publications
2
43
0
1
Order By: Relevance
“…In these atoms, O3 and O5 atoms from ligands which bridges two copper centers. While the two Cu centers are five-coordinated with one imino nitrogen atom, two oxygen atoms from Schiff-base ligands and the fourthly oxygen atoms from acetic molecule, consisting of the basal plane of square-pyramidal geometry and For complexes 3 and 5, the disordered solvate molecules are difficult to identify; correspondingly, solvate molecules were accounted for by using the program PLATON/SQUEEZE in order to remove the contributions of disordered solvent [29]. For details about the Squeezed material, see cif data in Supporting Information.…”
Section: Complexmentioning
confidence: 99%
“…In these atoms, O3 and O5 atoms from ligands which bridges two copper centers. While the two Cu centers are five-coordinated with one imino nitrogen atom, two oxygen atoms from Schiff-base ligands and the fourthly oxygen atoms from acetic molecule, consisting of the basal plane of square-pyramidal geometry and For complexes 3 and 5, the disordered solvate molecules are difficult to identify; correspondingly, solvate molecules were accounted for by using the program PLATON/SQUEEZE in order to remove the contributions of disordered solvent [29]. For details about the Squeezed material, see cif data in Supporting Information.…”
Section: Complexmentioning
confidence: 99%
“…have many applications, such as gas storage, molecular separation, catalysis, drug delivery, and so on [1][2][3][4][5]. Biphenyltetracarboxylates are excellent type of organic ligands for synthesizing various MOFs.…”
Section: Discussionmentioning
confidence: 99%
“…According to a Cambridge Structural Database (CSD, Version 5.38, May 2017; Groom et al, 2016) search, alkaline-earth metal-based CPs are less common compared to the reported transition metal and rare-earth metal CPs (Cai et al, 2017). Indeed, the study of alkaline-earth-metal systems is limited by challenges in the synthesis (Lian et al, 2016;Douvali et al, 2015;Mali et al, 2015;Chakraborty et al, 2014;Zhang, Huang et al, 2012;Liu, Tsao et al, 2010), the main reason being the variable coordination numbers (the most preferred coordination numbers are six for magnesium, six to eight for calcium, and six to twelve for strontium and barium), which lead to uncontrolled coordination geometries around the metal centre (Cai et al, 2016;Feng et al, 2015;Shi et al, 2015;Zheng et al, 2015;Jia et al, 2014;Zhang, Yuan et al, 2013;Smith et al, 2013;Zhai et al, 2013;Zhang, Guo et al, 2013;Deng et al, 2012;Foo et al, 2012;Xiao et al, 2012;Xie et al, 2012;Zhang, Luo et al, 2012;Jing et al, 2010;Zhang et al, 2010;Li et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recently, the interest in alkaline-earth metal ion-based CPs has been growing due to their unusual advantages such as low toxicity, wide distribution and low cost, which are of benefit for applications in the field of materials science (Raja et al, 2014;Foo et al, 2012Foo et al, , 2013Xiao et al, 2012 earth metal-based CPs are less common compared to the reported transition metal and rare-earth metal CPs (Cai et al, 2017). Indeed, the study of alkaline-earth-metal systems is limited by challenges in the synthesis (Lian et al, 2016;Douvali et al, 2015;Mali et al, 2015;Chakraborty et al, 2014;Zhang, Huang et al, 2012;Liu, Tsao et al, 2010), the main reason being the variable coordination numbers (the most preferred coordination numbers are six for magnesium, six to eight for calcium, and six to twelve for strontium and barium), which lead to uncontrolled coordination geometries around the metal centre (Cai et al, 2016;Feng et al, 2015;Shi et al, 2015;Zheng et al, 2015;Jia et al, 2014;Zhang, Yuan et al, 2013;Smith et al, 2013;Zhai et al, 2013 Besides, the ability of a system to bind alkaline-earth metal ions in aqueous solution is highly desirable and can be achieved thanks to the presence of oxygenated ligands and the preorganization of the receptor, which satisfies the need for a high coordination number without specific coordination requirements.Ligand L1 {4,10-bis[(3-hydroxy-4-pyron-2-yl)methyl]-1,7-dimethyl-1,4,7,10-tetraazacyclododecane} is a Maltol-based macrocycle (Amatori et al, 2012) II heterodinuclear metal coordination compound of L1, where a one-dimensional wave-like infinite array of barium ions bridges the [Co(H -2 L1)] moieties through a barium-2 -oxygen motif. This is the first time that L1 has proven able to form a coordination polymer and, to our knowledge, this is the first example of a macrocyclic ligand forming a Ba II -based 1D-CP containing Co II ions surrounded by an N 4 O 2 donor set.…”
mentioning
confidence: 99%